On the Solutions of a Third Order Rational Difference Equation: Raafat Abo-Zeid, Hossam Kamal
In this paper, we discuss the global behavior of all admissible solutions of the difference equation x_n+1=Ax_n-2 B- Cx_nx_n-1x_n-2 ,n=0,1,…, where A,B,C are positive real numbers and the initial conditions x_-2,x_-1,x_0 are real numbers. , number=4, journal=Thai Journal of Mathematics, author=Team, Support, year=2020, month=Dec., pages=1865–1874